Current advances of the sausage technique in bone augmentation - ZHOU Yanmin, LIU Xiuyu, CHEN Siyu (口腔疾病防治)
Sufficient bone tissue is required to ensure the long-term stability of implants. Based on the principles of guided bone regeneration, Dr. Istvan Urban proposed the “sausage technique”. Research indicates that the horizontal bone augmentation observed with the sausage technique averages (5.3 ± 2.3) mm and the vertical bone augmentation averages (4.2 ± 1.9) mm, which is significantly greater than the outcomes achieved with traditional guided bone regeneration techniques. The sausage technique is reliable because the biological membrane has sufficient elasticity and toughness with the application of membrane screws, which stabilizes the mixture of autologous bone and bone graft materials in the bone grafting area and prevents the grafting materials from being displaced. Using substitute materials for autologous bone graft balances the osteogenic activity and the low graft absorption rate. A ball drill is used to prepare nourishing holes in the cortical bone of the recipient area, providing a pathway for mesenchymal stem cells and bone progenitor cells to migrate to the bone regeneration area. Furthermore, this method accelerates the early angiogenesis of wound healing, fully reduces tension during suturing, and ensures that excessive pressure is not applied to the healing area during suturing. Thus, the sausage technique is consistent and reliable. Despite the good outcomes demonstrated by the sausage technique in clinical applications, its potential complications related to soft and hard tissue have attracted widespread attention. These complications negatively affect the patient’s recovery process and influence the final results of the surgery. Therefore, a complete understanding of the complications associated with the sausage technique and their underlying causes is necessary to enhance the clinical safety and effectiveness of the sausage technique. This article summarizes the application principles, clinical effects, barrier membrane applications, selection of bone transplant materials, and related complications of the sausage technique, aiming to provide a reference for clinical application.